Behavior of Mask Use in Patients' Families During the Pandemic at Bangil Hospital, Pasuruan Regency - Titiek Idayanti; Rahma Fauziah (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
At the beginning of the 2020 coronavirus pandemic, the World Health Organization (WHO) stated that the use of masks was recommended only for sick people, not for healthy people. However, the development of the virus finally prompted WHO to appeal to everyone (healthy and sick) to always use masks outside the home in a qualitative descriptive research design with a sample of 50 respondents. Interview guide with research subjects, namely families of patients who are hospitalized or outpatient at RSUD Bangil as the instrument. Results : Based on the interview results, the majority of respondents had sufficient information about masks. Most respondents do not wear masks / masks are removed according to their wants and needs, because most occur due to stress or difficulty breathing.